2020
DOI: 10.1093/ecco-jcc/jjaa081
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Endoscopic Recurrence in Crohn’s Disease Is Characterised by Distinct Microbiota Recolonisation

Abstract: Background and Aims Intestinal microbiota dysbiosis is implicated in Crohn’s disease [CD] and may play an important role in triggering postoperative disease recurrence [POR]. We prospectively studied faecal and mucosal microbial recolonisation following ileocaecal resection to identify the predictive value of recurrence-related microbiota. Methods Mucosal and/or faecal samples from 121 CD patients undergoing ileocaecal resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 51 publications
0
80
2
2
Order By: Relevance
“…Strömbeck et al detected higher Actinobacteria and lower Alistipes counts in the fecal microbiota of the PR group at their 1-year follow-up; Alistipes was found to correlate negatively with the Rutgeerts score ( 25 ). In another study tracking the trends in the fecal microbiota changes in patients with endoscopic recurrence, the relative Fusobacterium and Bifidobacterium abundances increased and decreased, respectively, in 1, 3, and 6 months after surgery compared to that in patients in remission ( 26 ). In addition, Hamilton et al found that bacterial clusters enriched with Enterobacteriaceae and Lachnospiraceae were associated with an increased risk of disease recurrence and the maintenance of remission, respectively ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strömbeck et al detected higher Actinobacteria and lower Alistipes counts in the fecal microbiota of the PR group at their 1-year follow-up; Alistipes was found to correlate negatively with the Rutgeerts score ( 25 ). In another study tracking the trends in the fecal microbiota changes in patients with endoscopic recurrence, the relative Fusobacterium and Bifidobacterium abundances increased and decreased, respectively, in 1, 3, and 6 months after surgery compared to that in patients in remission ( 26 ). In addition, Hamilton et al found that bacterial clusters enriched with Enterobacteriaceae and Lachnospiraceae were associated with an increased risk of disease recurrence and the maintenance of remission, respectively ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, increased Corynebacterium and decreased Ruminiclostridium 6 counts at baseline were identified as predictive factors of endoscopic recurrence for CD patients ( 27 ). Machiels et al reported that the Ralstonia, Haemophilus, Gemella , and Phascolarctobacterium abundances in resected specimens were good predictors using C5.0 classification tree analyses or random forest models ( 26 ). However, the considerable predictive power of Coprobacillus, unidentified Lachnospiraceae , and Dorea obtained from fecal samples before surgery could not be confirmed after validation using the forest model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With recent emerging data on intestinal microbiome dysbiosis in the colonized neo-terminal ileum affecting POR, it has been postulated that modulation with antibiotics or probiotics may have a role in the management of postoperative CD. [35][36][37] Of these, nitroimidazoles have been well studied and demonstrated benefit. Compared with placebo, metronidazole (20 mg/ kg) reduces endoscopic recurrence at 3 months after surgery (13% versus 43%, p = 0.02) and clinical recurrence at 1 year (4% versus 25%, p = 0.04).…”
Section: Antibioticsmentioning
confidence: 99%
“…85,86 Finally, microbiome dysbiosis is being recognized as a risk factor with recolonization of microbiota, including Proteobacteria, Akkermansia spp., Fusobacteriaceae and a depletion of Streptococcaceae, Actinomycineae, Faecalibacterium. [35][36][37] Interestingly, active smoking was associated with elevated levels of Proteus, 37 and thus these risk factors may be interactive. The role of other "-omics", including ileal tissue transcriptomics, blood transcriptomics, and urinary metabolomics, is being evaluated.…”
Section: Risk Factors and Stratification For Postoperative Recurrencementioning
confidence: 99%